Optimised sustainable energy supply alternatives for Libyan utilities under unsubsidised tariff conditions - Feras Alasali; Mohamed Almaktar; William Holderbaum (International Journal of Sustainable Energy)
With growing electricity demand and fossil fuel concerns, renewable energy (RE) solutions are becoming increasingly important. This paper explores sustainable energy alternatives to address the critical energy instability at an educational utility, namely the College of Electrical and Electronics Technology (CEET) in Benghazi, with potential applications for different Libyan sectors, including community areas and commercial entities. Four configurations were evaluated: standalone PV with storage, hybrid PV/wind/storage, grid-connected PV, and grid/diesel. The study aims to identify the optimal setup by minimising the net present cost (NPC) and levelised cost of energy (LCOE) over the project's operational period across varying fossil electricity and diesel rates. Sensitivity analysis indicates that higher diesel and grid electricity prices ($1.00/L and $0.10/kWh) reduce the LCOE of the hybrid system to $0.12/kWh, making it competitive with grid-based options. The study provides practical insights into addressing Libya's energy challenges using technically and economically feasible RE strategies.